1986
DOI: 10.1152/jn.1986.56.4.934
|View full text |Cite
|
Sign up to set email alerts
|

Unit study of monkey frontal cortex: active localization of auditory and of visual stimuli

Abstract: The influence of sound localization behavior on unit activity in the frontal cortex of awake rhesus monkeys was examined by comparing responses under three behavioral conditions: auditory localization, during which a response was required to the location of a sound (broad-band noise) source; auditory detect, during which a response was required to indicate the occurrence of the sound regardless of location; visual localization, during which no sounds were presented and a response was required to the location o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(84 citation statements)
references
References 0 publications
5
78
1
Order By: Relevance
“…Furthermore, Wise and collaborators (Mauritz and Wise, 1986;Vaadia et al, 1988;di Pellegrino and Wise, 1993a) described an anticipatory activity in PMd preceding relevant sensory cues, even when the movement was to be executed after a subsequent delay of up to several seconds. Such anticipatory activity was also reported in other areas, including parietal area 5 (MacKay and Crammond, 1987), the frontal cingulate cortex (Niki and Watanabe, 1979), the dorsal prefrontal cortex (Vaadia et al, 1986;Niki and Watanabe, 1987), and M1 (Crammond and Kalaska, 1996;Fig. 3 in Roux et al, 2003).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, Wise and collaborators (Mauritz and Wise, 1986;Vaadia et al, 1988;di Pellegrino and Wise, 1993a) described an anticipatory activity in PMd preceding relevant sensory cues, even when the movement was to be executed after a subsequent delay of up to several seconds. Such anticipatory activity was also reported in other areas, including parietal area 5 (MacKay and Crammond, 1987), the frontal cingulate cortex (Niki and Watanabe, 1979), the dorsal prefrontal cortex (Vaadia et al, 1986;Niki and Watanabe, 1987), and M1 (Crammond and Kalaska, 1996;Fig. 3 in Roux et al, 2003).…”
Section: Introductionmentioning
confidence: 56%
“…The primary motor cortex (M1) and dorsal premotor cortex (PMd) are activated during movement execution (Weinrich et al, 1984(Weinrich et al, , 1985Requin, 1989, 1995;Crammond and Kalaska, 1996), but also beforehand, as the animal prepares to move (Wise and Mauritz, 1985;Wise and Kurata, 1989;Shen and Alexander, 1997a,b;Riehle, 2005), and after the presentation of relevant visual cues (Godschalk et al, 1981;Vaadia et al, 1986;Riehle and Requin, 1989;Miller et al, 1992;Boussaoud and Wise, 1993a,b;Kalaska, 1996, 2000;Yamagata et al, 2009). Furthermore, Wise and collaborators (Mauritz and Wise, 1986;Vaadia et al, 1988;di Pellegrino and Wise, 1993a) described an anticipatory activity in PMd preceding relevant sensory cues, even when the movement was to be executed after a subsequent delay of up to several seconds.…”
Section: Introductionmentioning
confidence: 99%
“…A somatosensory region in the ventral LPFC of humans (Kostopoulos et al, 2007) in which neurons reflect the frequency of vibrotactile stimuli has been identified (Romo et al, 1999). Wide regions in the LPFC receive specific inputs from auditory areas in the superior temporal cortex (Hackett et al, 1999;Romanski et al, 1999a,b), and functional specialization has been demonstrated between the dorsal and the ventral LPFCs (Vaadia et al, 1986;Romanski et al, 1999b;Kikuchi-Yorioka and Sawaguchi, 2000;Romanski and Goldman-Rakic, 2002;Cohen et al, 2004;Sugihara et al, 2006;Russ et al, 2008;Cohen et al, 2009). In the current study, we observed a widespread distribution of auditory neurons without a clear functional segregation, which was reasonable because we asked the animals to detect the onset of a simple auditory signal.…”
Section: Encoding Of Sensory Signals By Lpfc Neuronsmentioning
confidence: 99%
“…The SEF is an oculomotor field that can be identified with intracortical microstimulation and that, anatomically, is richly connected with the frontal eye field (FEF). The remaining part of F7 is scarcely excitable and has been object of few functional studies (Vaadia et al, 1986;di Pellegrino and Wise, 1991;Fuji et al, 2000). Some F7 neurons have visual responses even when the stimulus is not instructing a subsequent movement.…”
Section: S28mentioning
confidence: 99%